Upload

QA #4 Factors and Multipless

background image

Questions and Answers Sheet 4

 

                                  Factors and Multiples 

 

Question #1 

Simplify. Assume that all variables result in nonzero denominators. 
Enter the expression in simplest form. The numerator and denominator must be in explanded form (i.e. 
not a product of factors). 

 

⇒

6𝑞

𝑞+1

−

𝑞−4

𝑞

+

6

𝑞+1

=

 

 

Answer: 

 

⇒

6𝑞

𝑞+1

−

𝑞−4

𝑞

+

6

𝑞+1

  ⇒

6𝑞

2

−(𝑞−4)(𝑞+1)+6𝑞

𝑞(𝑞+1)

  

 

⇒

6𝑞

2

−(𝑞

2

+𝑞−4𝑞−4)+6𝑞

𝑞(𝑞+1)

  

 

⇒

6𝑞

2

−(𝑞

2

−3𝑞−4)+6𝑞

𝑞(𝑞+1)

  

⇒

6𝑞

2

− 𝑞

2

+ 3𝑞 + 4 + 6𝑞

𝑞(𝑞 + 1)

 

 

⇒

5𝑞

2

+9𝑞+4

𝑞(𝑞+1)

  

 

⇒

5𝑞

2

+5𝑞+4𝑞+4

𝑞(𝑞+1)

  

 

⇒

5𝑞(𝑞+1)+4(𝑞+1)

𝑞(𝑞+1)

  

 

⇒

(5𝑞+4)(𝑞+1)

𝑞(𝑞+1)

  

 

⇒

5𝑞+4

𝑞

  

So, the simplified expression is: 

 

⇒

5𝑞+4

𝑞

 

 

Question #2 

Write the exprissuon as a sum and/or difference of logarithms. 

 

log (

7√𝑥+3

𝑥

4

(𝑥−5)

2

) 𝑥 > 5

  

Answer: 

Now  

log (

7√𝑥+3

𝑥

4

(𝑥−5)

2

) 𝑥 > 5

  

 

= log(7√𝑥 + 3) − log(𝑥

4

(𝑥 − 5)

2

) [∵ log (

𝑚

𝑛

) = log 𝑚 − log 𝑛]

  

 

= log(7) + log(√𝑥 + 3) − log(𝑥4) − log(𝑥 − 5)

2

[log(𝑚𝑛) = log 𝑚 + log 𝑛]

  

 

= log(7) +

1

2

log(𝑥 + 3)

1/2

− 4 log 𝑥 − 2 log(𝑥 − 5) [log 𝑥

𝑚

= 𝑚 log 𝑥]

  

 

= log(7) +

1

2

log(𝑥 + 3) − 4 log 𝑥 − 2 log(𝑥 − 5)

  

Hence  

log (

7√𝑥+3

𝑥

4

(𝑥−5)

2

) = log(7) +

1

2

log(𝑥 + 3) − 4 log 𝑥 − 2 log(𝑥 − 5)

 

 

background image

Question #3 

Canning Tomato Products. Jaeger Foods produces tomato sauce and tomato paste, canned in small, 

medium, large, and giant-sized cans. The matrix A 

4 1

4

0

7

28

0

8

32

4

0

0

28 0

0

32

1

0

0

7

0

0

8

0

−

−

−

−

−

−

gives the size 

(in ounces) of each container. 

 

6

10

14

28

Small

Medium

Large

Giant

Ounces

A

=

 

The matrix B tabulates one day's production of tomato sauce and tomato paste. 

 

2000

2500

3000

1500

2500

1000

1000

500

Cans of sauce

Cans of paste

Small

Medium

B

Large

Giant

=

  

a) Calculate the product AB. 

b) Interpret the entries in the product matrix AB.

 

Answer: 

Step 1 

Matrix, a set of numbers arranged in rows and columns so as to form a rectangular array. The numbers 

are called the elements, or entries, of the matrix. 

And by using the product of the matrix  

4  × 1

  and  

2  × 4

  will result the matrix of  

2  × 1

 . 

 





2000

2500

3000 1500

6 10 14

28

2500 1000

1000

500

AB

AB













=



=













  

Step 2 

Now multiply the row of the A matrix with the first column of the matrix B and keep on adding the multiples 

then multiply the row of the A matrix with the second column of the matrix B and keep on adding the 

multiples. 

 





2000

2500

3000 1500

6 10 14

28

2500 1000

1000

500

AB

AB













=



=













 

 

= [(6 × 2000) + (10 × 3000) + (14 × 2500) + (28 × 1000)(6 × 2500) + (10 × 1500) + (14 × 1000) +

(28 × 500)]

  

 

= [12000 + 30000 + 35000 + 2800015000 + 15000 + 14000 + 14000]

  

 

= [10500058000]

 

 

Question #4 

background image

A polynomial and one of its factors is given. Factor the polynomial COMPLETELY given that one of its 

factors is  

𝑥 + 4

 . Your final answer should be in factored form. 

𝑓(𝑥) = 𝑥

7

+ 4𝑥

6

+ 7𝑥

4

+ 28𝑥

3

− 8𝑥 − 32

 

 

Answer: 

Step 1 

We use the synthetic division to get the other factor for the missing terms, we will use 0 as the coefficient. 

 

4 1

4

0

7

28

0

8

32

4

0

0

28 0

0

32

1

0

0

7

0

0

8

0

−

−

−

−

−

−

 

So the quotient is  

𝑥

6

+ 7𝑥

3

− 8

  

Step 2 

Then we try to factor  

𝑥

6

+ 7𝑥

3

− 8

  

 

𝑥

6

+ 7𝑥

3

− 8

  

 

= (𝑥

3

+ 8)(𝑥

3

− 1)

  

 

= (𝑥^{3} + 2^{3})(𝑥

3

− 1

3

)  

 

= (𝑥 + 2)(𝑥

2

− 2𝑥 + 4)(𝑥 − 1)(𝑥

2

+ 𝑥 + 1)

  

Answer:  

(𝑥 + 4)(𝑥 + 2)(𝑥

2

− 2𝑥 + 4)(𝑥 − 1)(𝑥

2

+ 𝑥 + 1)

 

 

Question #5 

Write the following expression as a sum and/or difference of logarithms. Express powers as factors. 

 

log

𝑑

(𝑢

8

𝑣

3

) 𝑢 > 0, 𝑣 > 0

  

 

log

𝑑

(𝑢

8

𝑣

3

) =?

  (Simplify your answer.)

 

Answer: 

Step 1 

It is required to write the expression as a sum or difference of logarithms. 

The given expression is:  

log

𝑑

(𝑢

8

𝑣

3

)

  

Step 2 

Use property:  

log

𝑑

(𝑎 ⋅ 𝑏) = log

𝑑

(𝑎) + log

𝑑

(𝑏)

  

Step 3 

Now, apply the above property to simplify: 

 

log

𝑑

(𝑢

8

𝑣

3

) = log

𝑑

(𝑢

8

) + log

𝑑

(𝑣

3

)

  

Step  

Now use the property:  

log

𝑑

(𝑥

𝑛

) = 𝑛 log

𝑑

(𝑥)

  

Step 5 

By applying the property expression reduces to: 

 

log

𝑑

(𝑢

8

𝑣

3

) = log

𝑑

(𝑢

8

) + log

𝑑

(𝑣

3

)

  

 

log

𝑑

(𝑢

8

𝑣

3

) = 8 log

𝑑

(𝑢) + 3 log

𝑑

(𝑣)

 

 

Question #6 

Simplify. 

background image

 

1+

2

𝑥+4

1+

9

𝑥−3

  

Step 1: Find the LCM of the denominators of the fractions in the numerator and denominator. 

Step 2: Multiply the numerator and denominator of the complex fraction by the LCM. 

Step 3: Factor  

𝑥−3

𝑥+4

  

Step 4: Divide out common factors.

 

Answer: 

Given fraction is: 

 

1+

2

𝑥+4

1+

9

𝑥−3

  

To simplify the given fraction. 

Step1. Find the LCM of the denominators of the fractions in numerators and denominators 

 

1+

2

𝑥+4

1+

9

𝑥−3

=

(𝑥+4)+2

(𝑥+4)

(𝑥−3)+9

(𝑥−3)

  

 

(𝑥+6)
(𝑥+4)
(𝑥+6)

𝑥−3

  

Step 2. Multiply the numerator and denominator of the complex fraction by the LCM. 

 

(𝑥+6)
(𝑥+4)
(𝑥+6)

𝑥−3

=

(𝑥+6)×(𝑥−3)
(𝑥+4)×(𝑥+6)

  

Step 3. Factor 

 

(𝑥+6)×(𝑥−3)
(𝑥+4)×(𝑥+6)

  

Step 4. Divide out common factors 

 

(𝑥+6)×(𝑥−3)
(𝑥+4)×(𝑥+6)

= (

𝑥−3

𝑥+4

)

  

Thus, the simplified form is  

(

𝑥−3

𝑥+4

)

.

 

Question #7 

Determine the lowest common multiple (LCM) and the highest common factor (HCF) of the following 

algebraic terms by using ' factors: 

 

22𝑎

5

𝑏

3

𝑐

2

; 2𝑎

4

𝑏

4

𝑐

3

; 4𝑎

2

𝑏

2

𝑐

5

 

 

Answer: 

Step 1 

Given , 

 

𝑋 = 22𝑎

5

𝑏

3

𝑐

2

  

 

𝑌 = 2𝑎

4

𝑏

4

𝑐

3

  

 

𝑍 = 4𝑎

2

𝑏

2

𝑐

5

  

Step 2 

 

22𝑎

5

𝑏

3

𝑐

2

; 2𝑎

4

𝑏

4

𝑐

3

; 4𝑎

2

𝑏

2

𝑐

5

  

Let  

𝑥 = 2 × 11 × 𝑎

5

× 𝑏

3

× 𝑐

2

  

 

𝑦 = 2 × 𝑎

4

× 𝑏

4

× 𝑐

3

  

background image

 

𝑧 = 2 × 2 × 𝑎

2

× 𝑏

2

× 𝑐

5

  

 

𝐿𝐶𝑀 = 2 × 11 × 2 × 𝑎

5

× 𝑏

4

× 𝑐

5

  

 

𝐿𝐶𝑀 = 44𝑎

5

𝑏

4

𝑐

5

  

 

𝐻𝐶𝐹 = 2 × 𝑎

2

× 𝑏

2

× 𝑐

2

  

 

𝐻𝐶𝐹 = 2𝑎

2

𝑏

2

𝑐

2

 

 

Question #8 

Write the expression as a sum and/or difference of logarithms. Express powers as factors. 

 

ln

2𝑥√1+8𝑥

(𝑥−3)

13

, 𝑥 > 3

  

 

ln

2𝑥√1+8𝑥

(𝑥−3)

13

=

  (Simplify your answer.)

 

Answer: 

Step 1 

The given expression is  

 

ln

2𝑥√1+8𝑥

(𝑥−3)

13

, 𝑥 > 3

  

Step 2 

Using the formula 

 

ln (

𝑎

𝑏

) = ln 𝑎 − ln 𝑏

  

 

ln(𝑎𝑏) = ln 𝑎 + ln 𝑏

  

 

ln 𝑎

𝑛

= 𝑛 ln 𝑎

 

Step 3 

On simplifying with the help of given formula 

 

ln

2𝑥√1+8𝑥

(𝑥−3)

13

= ln

2𝑥(1+8𝑥)

1
2

(𝑥−3)

13

  

 

= ln 2 𝑥(1 + 8𝑥)

1
2

− ln(𝑥 − 3)

13

  

 

= ln 2 𝑥 + ln(1 + 8𝑥)

1
2

− ln(𝑥 − 3)

13

  

 

= ln 2 𝑥 + ln(1 + 8𝑥)

1
2

− ln(𝑥 − 3)

13

  

 

= ln 2 + ln 𝑥 +

1

2

ln(1 + 8𝑥) − 13 ln(𝑥 − 3)

  

 

⇒ ln

2𝑥√1+8𝑥

(𝑥−3)

13

= ln 2 + ln 𝑥 +

1

2

ln(1 + 8𝑥) − 13 ln(𝑥 − 3)

 

 

Question #9

 

To simplify the expression,  

√23

 .

 

Answer:

 

Concept used: 

To simplify an expression having square root of a number, firstly factorization of the number is done and 

then factors having even exponential powers are taken out from the square root function and their 

exponential powers are divided by two. 

 

⇒ √𝑚

4

× 𝑛

2

= 𝑚

4
2

× 𝑛

2
2

= 𝑚

2

× 𝑛

1

  

background image

Calculations: 

As per the question, the expression is  

√23

 . 

The factorization of a number is the product of numbers that equals the number. 

Now, 23 is a ' number. Hence, it has only two multiples i.e. 1 and 23. 

Therefore, 12 cannot be factorized anymore. 

Hence, the simplified value of  

√23

 is  

√23

  only.

 

Question #10 

Write the expression as a sum and/or difference of logarithms. Express powers as factors. 

 

log [

𝑥(𝑥+4)

(𝑥+2)

5

] , 𝑥 > 0

  

 

log [

𝑥(𝑥+4)

(𝑥+2)

5

] =?

  (Simplify your answer.)

 

Answer: 

Step 1 

It is required to simplify the given expression: 

 

log [

𝑥(𝑥+4)

(𝑥+2)

5

]

  

Step 2 

Apply these properties of logarithm to simplify: 

 

log (

𝑎

𝑏

) = log(𝑎) − log(𝑏)

  

 

log(𝑎 ⋅ 𝑏) = log(𝑎) + log(𝑏)

  

 

log(𝑥

𝑛

) = 𝑛 log(𝑥)

 

Step 3 

Now, by using these properties simplify the given expression: 

 

log (

𝑥(𝑥+4)

(𝑥+2)

5

) = log(𝑥(𝑥 + 4)) − log((𝑥 + 2)

5

)

 

 

= log(𝑥) + log(𝑥 + 4) − 5 log(𝑥 + 2)

 

 

Question #11 

To calculate: The simplified value of the expression  

√32𝑥

16

𝑦

10

5

  using radical notation.

 

Answer:  

Formula used: 

From the product rule, 

 

√𝑎𝑏

𝑛

= √𝑎

𝑛

⋅ √𝑏

𝑛

  

Where a and b are positive number and n is larger than 1. 

Calculation: 

Consider the provided expression, 

 

√32𝑥

16

𝑦

10

5

  

Expand the expression by identifying the largest exponents and multiples of 5, 

 

√32𝑥

16

𝑦

10

5

= √2

5

⋅ 𝑥

15

⋅ 𝑥 ⋅ 𝑦

10

5

  

Now, separate the terms with fifth power factors by using the product rule, 

background image

 

√2

5

⋅ 𝑥

15

⋅ 𝑥 ⋅ 𝑦

10

5

= √2

5

5

⋅ √𝑥

15

5

⋅ √𝑥

5

⋅ √𝑦

10

5

  

Simplify it further, 

 

√2

5

5

⋅ √𝑥

15

5

⋅ √𝑥

5

⋅ √𝑦

10

5

= 2 ⋅ 𝑥

3

⋅ √𝑥

5

⋅ 𝑦

2

 

 

= 2𝑥

3

𝑦

2

√𝑥

5

 

Hence, the simplified value of expression is  

2𝑥

3

𝑦

2

√𝑥

5

 

 

Question #12 

a) Using the remainder theorem, determine whether  

(𝑥 − 4)

  and  

(𝑥 − 1)

  are factors of the expression  

𝑥

3

+ 3𝑥

2

− 22𝑥 − 24

 . 

b) Hence, by use of long division, find all remaining factors of the expression. 

Answer: 

Step 1 

Given:  

𝑥

3

+ 3𝑥

2

− 22𝑥 − 24

  

a)  

(𝑥 − 4)

  Factor  

𝑥 − 4 = 0

  

 

𝑥 − 4

  

 

(4)

3

+ 3(4)

2

− 22(4) − 24

  

 

= 64 + 48 − 88 − 24

  

 

= 112 − 112 = 0 

 

 

(𝑥 − 1)

  Factor  

𝑥 − 1 = 0

  

 𝑥 = 1

  

 

(1)

3

+ 3(1)

2

− 22(1) − 24

 

 

= 1 + 3 − 22 − 24

 

4

1

3

22

24

0

4

28

24

1

7

6

0

−

−

 

 

= 4 − 46

  

 

= −40

 (not a factor) 

Step 2 

b)  

(𝑥 − 4)

  Factor of  

𝑥

[3}

+ 3𝑥

2

− 22𝑛 − 24

 

 

𝑥 = 4

  

 

4

1

3

22

24

0

4

28

24

1

7

6

0

−

−

 

 

𝑥

2

+ 7𝑥 + 6

  

 

= 𝑥

2

+ 6𝑥 + 𝑥 + 6

  

 

= 𝑥(𝑥 + 6) + 1(𝑥 + 6)

  

 

= (𝑥 + 6)(𝑥 + 1)

  

 

(𝑥 + 6)(𝑥 + 1)

  are the remaining factors.

 

background image

Question #13

 

Given  

𝑃(𝑥) = 𝑥

3

+ 5𝑥

2

+ 25𝑥 + 125

 , find the zeros, real and non-real of 

𝑃

 . 

The zeros are 5. 

Write P in factored form (as a product of linear factors). Be sure to write the full equation, including  

𝑃(𝑥) =

.

 

Answer: 

Step 1 

Given  

𝑃(𝑥) = 𝑥

3

+ 5𝑥

2

+ 25𝑥 + 125

   

We have to write P in factored from 

Step 2 

given:  

𝑝(𝑥) = 𝑥

3

+ 5𝑥

2

+ 25𝑥 + 125

  

 

𝑝(𝑥) = (𝑥

3

+ 5𝑥

2

) + (25𝑥 + 125)

  

 

𝑝(𝑥) = 𝑥

2

(𝑥 + 5) + 25(𝑥 + 5)

  

 

𝑝(𝑥) = (𝑥

2

+ 25)(𝑥 + 5)

 

 

Question #14 

Given  

𝑃(𝑥) = 3𝑥

5

− 5𝑥

4

+ 37𝑥

3

− 83𝑥

2

− 176𝑥 − 48

 , and that 4i is a zero, write P in factored form (as a 

product of linear factors). Be sure to write the full equation, including  

𝑃(𝑥) =

 .

 

Answer: 

Step 1 

The given polynomial is: 

 

𝑃(𝑥) = 3𝑥

5

− 5𝑥

4

+ 37𝑥

3

− 83𝑥

2

− 176𝑥 − 48

  

Step 2 

Now  

𝑥  =  4𝑖

  is a zero of the given polynomial, therefore 

 𝑥  =   −4𝑖

  is also zero of the given polynomial. 

Therefore:  

(𝑥 − 4𝑖)(𝑥 + 4𝑖)

  divides the given polynomial. That is one of the factors of given polynomial 

is:  

𝑥2 + 16

  

 

𝑃(𝑥)

𝑥

2

+16

=

3𝑥

5

−5𝑥

4

+37𝑥

3

−83𝑥

2

−176𝑥−48

𝑥

2

+16

 

 

𝑃(𝑥)

𝑥

2

+16

= 3𝑥

3

− 5𝑥

2

− 11𝑥 − 3

  

 

𝑃(𝑥) = (𝑥

2

+ 16)(3𝑥

3

− 5𝑥

2

− 11𝑥 − 3)

  

 

𝑃(𝑥) = (𝑥

2

+ 16)(𝑥 + 1)(𝑥 − 3)(3𝑥 + 1)

 

 

Question #15 

Given  

𝑃(𝑥) = 3𝑥

5

− 𝑥

4

+ 81𝑥

3

− 27𝑥

2

− 972𝑥 + 324

 , and that 6i is a zero, write P in factored form (as a 

product of linear factors). Be sure to write the full equation, including  

𝑃(𝑥) =

 .

 

Answer: 

Step 1 

 

𝑃(𝑥) = 3𝑥

5

− 𝑥

4

+ 81𝑥

3

− 27𝑥

2

− 972𝑥 + 324

  

Given: 6i is a zero. 

background image

 

⇒ −6𝑖 

 is also a zero. 

 

⇒ (𝑥 + 6𝑖)(𝑥 − 6𝑖)

  in a factor 

 

⇒ (𝑥

2

+ 36)

  in a factor of P(x). 

Step 2 

 

𝑃(𝑥) = 3𝑥

5

− 𝑥

4

+ 81𝑥

3

− 27𝑥

2

− 972𝑥 + 324

  

 

= 𝑥

4

(3𝑥 − 1) + 27𝑥

2

(3𝑥 − 1) − 324(3𝑥 − 1)

  

 

= (3𝑥 − 1)(𝑥

4

+ 27𝑥

2

− 324)

  

 

= (3𝑥 − 1)[𝑥

2

(𝑥

2

+ 36) − 9(𝑥

2

+ 36)]

  

 

= (3𝑥 − 1)(𝑥

2

+ 36)(𝑥

2

− 9)

 

 

= (3𝑥 − 1)(𝑥

2

+ 36)(𝑥 + 3)(𝑥 − 3)

 

Factored form of P(x): 

 

𝑃(𝑥) = (3𝑥 − 1)(𝑥

2

+ 36)(𝑥 + 3)(𝑥 − 3)

 

 

Question #16 

Given  

𝑃(𝑥) = 3𝑥

5

− 4𝑥

4

+ 9𝑥

3

− 12𝑥

2

− 12𝑥 + 16

 , and that 2i is a zero, write P in factored form (as a 

product of linear factors). Be sure to write the full equation, including  

𝑃(𝑥) =

 .

 

Answer: 

 

𝑃(𝑥) = 3𝑥

5

− 4𝑥

4

+ 9𝑥

3

− 12𝑥

2

− 12𝑥 + 16

  

Given that, 

2i is a zero of P(x) 

 

∴ −2𝑖

  is also a zero of P(x) 

 

∴ (𝑥 − 2𝑖), (𝑥 + 2𝑖)

  are two factors of P(x) 

Now  

(𝑥 − 2𝑖)(𝑥 + 2𝑖) = 𝑥

2

− (2𝑖)

2

  

 

= 𝑥

2

− 4𝑖

2

  

 

𝑥

2

+ 4

  

 

∴ 𝑃(𝑥) = 3𝑥

5

− 4𝑥

4

+ 9𝑥

3

− 12𝑥

2

− 12𝑥 + 16

  

 

= 3𝑥

3

(𝑥

2

+ 4) − 4𝑥

2

(𝑥

2

+ 4) − 3𝑥(𝑥

2

+ 4) + 4(𝑥

2

+ 4)

  

 

= (𝑥

2

+ 4)(3𝑥

3

− 4𝑥

2

− 3𝑥 + 4)

  

 

= (𝑥

2

+ 4)[3𝑥

2

(3𝑥 − 4) − 1(3𝑥 − 4)]

  

 

= (𝑥

2

+ 4)(3𝑥 − 4)(𝑥

2

− 1)

  

 

= (𝑥

2

+ 4)(3𝑥 − 4)(𝑥 + 1)(𝑥 − 1)

  

 

= (𝑥 + 2𝑖)(𝑥 − 2𝑖)(3𝑥 − 4)(𝑥 + 1)(𝑥 − 1)

  

For zeros, 

 

𝑃(𝑥) = 0

  

 

⇒ 3𝑥

5

− 4𝑥

4

+ 9𝑥

3

− 12𝑥

[2}

− 12𝑥 + 16 = 0

 

 

⇒ (𝑥 + 2𝑖)(𝑥 − 2𝑖)(3𝑥 − 4)(𝑥 + 1)(𝑥 − 1) = 0

  

 

∴ 𝑍𝑒𝑟𝑜𝑠𝑜𝑓𝑃(𝑥)

 are 

 

−2𝑖, 2𝑖,

4

3

, −1,1

 .

 

background image

Question #17 

Given  

𝑃(𝑥) = 3𝑥

5

− 8𝑥

4

+ 35𝑥

3

− 98𝑥

2

− 208𝑥 + 480

 , and that 4i is a zero, write P in factored form (as a 

product of linear factors). Be sure to write the full equation, including  

𝑃(𝑥) =

 

 

Answer: 

Step 1 

Given:  

𝑃(𝑥) = 3𝑥

5

− 8𝑥

4

+ 35𝑥

3

− 98𝑥

2

− 208𝑥 + 480

  

It is given that 4i is a zero of P(x) 

We know that for polynomials with real coefficients, the complex zeros always exists in conjugate pairs 

Hence, -4i is also a zero of P(x) 

Hence,  

(𝑥 − 4𝑖), (𝑥 + 4𝑖)

  are factors of P(x) 

So,  

(𝑥 − 4𝑖)(𝑥 + 4𝑖)

  is a factor of P(x) 

 

⇒ 𝑥

2

+ 16

  is a factor of P(x) 

Dividing P(x) by  

𝑥

2

+ 16

  

So, 

3𝑥

5

−8𝑥

4

+35𝑥

3

−98𝑥

2

−208𝑥+480

𝑥

2

+16

= 3𝑥

3

− 8𝑥

2

− 13𝑥 + 30

 

 

𝑃(𝑥) = (3𝑥

3

− 8𝑥

2

− 13𝑥 + 30)(𝑥

2

+ 16)

  

Step 2 

Consider  

𝐹(𝑥) = 3𝑥

3

− 8𝑥

2

− 13𝑥 + 30

  

We observe that  

𝐹(−2) = 3(−2)

3

− 8(−2)

2

− 13(−2) + 30

  

 

𝐹(−2) = −24 − 32 + 26 + 30

  

 

𝐹(−2) = 0

  

Similarly,  

𝐹(3) = 0

  

So, -2,3 are zeros of F(x) and hence of P(x) too 

Let  

𝛼

  be the fifth zero of P(x) 

We know that the sum of zeros of  

𝑃(𝑥) = 8/3

  

 

𝛼 + 4𝑖 − 4𝑖 + (−2) + (3) =

8

3

  

 

𝛼 =

8

3

− 1

  

 

𝛼 =

5

3

 

Hence, the zeros are  

−2,3,4𝑖, −4𝑖,

5

3

  

Hence,  

𝑃(𝑥) = 3(𝑥 + 2)(𝑥 − 3)(𝑥 − 4𝑖)(𝑥 + 4𝑖) (𝑥 −

5

3

)

 

 

Question #18 

To solve the given equation for x. 

Given equation:  

log

3

(𝑥

2

− 𝑥 − 6) − log

3

(𝑥 − 3) = 1

 

 

Answer: 

Concept used: 

Quotient property of logarithm:  

log

𝑎

𝑏 − log

𝑎

𝑐 = log

𝑎

(

𝑏

𝑐

)

  

 

log

𝑎

𝑎 = 1

 . 

background image

Calculation: 

 

log

3

(

𝑥

2

−𝑥−6

𝑥−3

) = 1

  

Next step is no factor the numerator 

𝑥

2

− 𝑥 − 6

. 

To factorize the above trinomial, first step is to find the two multiples of the constant term -6 so that their 

addition will result the coefficient of x which is -1. 

So,  

6 = (−3) ⋅ (2)

  

Addition of -3 and 2 will result -1. 

So, the factors form of: 

 

𝑥

2

− 𝑥 − 6 = (𝑥 − 3)(𝑥 + 2)

  

Hence, the equation will be: 

 

log

3

(

(𝑥−3)(𝑥+2)

𝑥−3

) = 1

  

 

log

3

(𝑥 + 2) = 1

  Cancel out  

(𝑥 − 3)

  from both numerator and denominator. 

𝑙𝑜𝑔

3

(𝑥 + 2) = 𝑙𝑜𝑔

3

3

 Since, 

log

𝑎

𝑎 = 1

. 

 𝑥 + 2 = 3

  

 

𝑥 + 2 − 2 = 3 − 2

  By subtracting 2 from each sides of the equation. 

 

𝑥 = 1 

.

 

Question #19 

Carla used a calculator and found out that  

31.5  × 21.68 = 682.92 

. She is suspicious about her answer 

because it doesn't have three decimal places in it. Explain to her why the answer is correct by reasoning 

about the size of the factors, and also why her answer doesn't have  2+1=3  decimal places.

 

Answer: 

Step 1 

 

31.5  × 21.68  =  682.92

  

We know that  

3  × 2  =  6

  

Also,  

30  × 20  =  600

  

Thus solution should be  

> 600

 . 

Step 2 

Also, 8 (which is the last decimal digit of 21.68)  

× 5

  (which is the last decimal digit of 31.5)  

=  40

 . This 0 

cancels the 3rd decimal digit in the answer. Thus, the solution has 2 decimal digits.

 

Question #20 

To solve the given equation for x. 

Given equation: 

log

5

(𝑥

2

− 5𝑥 + 6) − log

5

(𝑥 − 2) = 1

 

 

Answer: 

Concept used: 

Quotient property of logarithm:  

log

𝑎

𝑏 − log

𝑎

𝑐 = log

𝑎

(

𝑏

𝑐

)

  

 

log

𝑎

𝑎 = 1

 . 

Calculation: 

background image

 

log

5

(

𝑥

2

−5𝑥+6

𝑥−2

) = 1

  

Next step is no factor the numerator  

𝑥

2

− 5𝑥 + 6

 . 

To factorize the above trinomial, first step is to find the two multiples of the constant term 6 so that their 

addition will result the coefficient of x which is -5. 

So,  

6 = (−3) ⋅ (2)

 

Addition of -3 and 2 will result -5. 

So, the factors form of: 

 

𝑥

2

− 5𝑥 + 6 = (𝑥 − 3)(𝑥 − 2)

  

Hence, the equation will be: 

 

log

5

(

(𝑥−3)(𝑥−2)

𝑥−2

) = 1

  

 

log

5

(𝑥 − 3) = 1

  Cancel out  (x-2)  from both numerator and denominator. 

 

𝑙𝑜𝑔

5

(𝑥 − 3) = 𝑙𝑜𝑔

5

5

  Since,  

log

𝑎

𝑎 = 1

 . 

 

𝑥 − 3 = 5

  

 

𝑥 − 3 + 3 = 5 + 3

  By adding 3 from each sides of the equation. 

 𝑥 = 8

 . 

of 12